EXISTENT MOTIVATION IN THE STORY OF "THE SHOT" - Muminova Gavxaroy; Pardaeva Dilfuza (Galaxy International Interdisciplinary Research Journal, 2022)
In this state rassmatrivayutsya key aspects of the system of existential motives in the story "Otstavshiy", as well as the multifaceted author’s interpretations.In tvorchestve Makanina takje mojno prosledit ekzistentsialnuyu problematiku, kotoraya vыrajaetsya v momentu otchayaniya, napryajennyx chuvstv, stradaniy ego geroev. In proizvedeniyax Makanina existential problem rassmatrivaetsya in the process of depiction of man in time vzaimootnosheniy s drugimi lyudmi.